Cross-resistance to acetolactate synthase (ALS) inhibitors associated with different mutations in Japanese foxtail (Alopecurus japonicus). Issue 4 (July 2019) - Zhao, Ning; Bi, Yaling; Wu, Cuixia; Wang, Dandan; You, Ludan; Liu, Weitang; Wang, Jinxin
Abstract: Japanese foxtail ( Alopecurus japonicus Steud.) is an invasive grass weed that severely threatens the production of wheat ( Triticum aestivum L.) and canola ( Brassica napus L.) crops in eastern Asia. Mesosulfuron-methyl is a highly efficient acetolactate synthase (ALS)-inhibiting herbicide widely used for control of this species in China. However, in recent years, some A. japonicus populations have evolved resistance to mesosulfuron-methyl by different amino acid substitutions (AASs) within the ALS gene. In the current study, 11 populations of A. japonicus were collected from Anhui Province, China, where the wheat fields were severely infested with this weed. Based on single-dose screening, eight of these populations evolved resistance to mesosulfuron-methyl, and gene sequencing revealed three AASs located in codon 197 or 574 of the ALS gene in the different resistant populations. Subsequently, three typical populations, AH-1, AH-4, and AH-10 with Trp-574-Leu, Pro-197-Thr, and Pro-197-Ser mutations, respectively, in ALS genes were selected to characterize their cross-resistance patterns to ALS inhibitors. Compared with the susceptible population AH-S, AH-1 showed broad-spectrum cross-resistance to sulfonylureas (SUs), imidazolinones (IMIs), triazolopyrimidines (TPs), and sulfonyl-aminocarbonyl-triazolinones (SCTs); whereas AH-4 and AH-10 were resistant to SUs, TPs, and SCTs but sensitive to IMIs. Moreover, all three resistant populations were sensitive to both photosystem II inhibitor isoproturon and 4-hydroxyphenylpyruvate dioxygenase inhibitor QYM201 (1-(2-chloro-3-(3-cyclopropyl-5-hydroxy-1-methyl-1H-pyrazole-4-carbonyl)-6-(trifluoromethyl)phenyl)piperidin-2-one). Based on the current state of knowledge, this study is the first report of A. japonicus evolving cross-resistance to ALS-inhibiting herbicides due to a Pro-197-Ser mutation in the ALS gene.